2010
DOI: 10.1038/cr.2010.159
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-κB in the skeleton

Abstract: Since the discovery that deletion of the NF-κB subunits p50 and p52 causes osteopetrosis in mice, there has been considerable interest in the role of NF-κB signaling in bone. NF-κB controls the differentiation or activity of the major skeletal cell types -osteoclasts, osteoblasts, osteocytes and chondrocytes. However, with five NF-κB subunits and two distinct activation pathways, not all NF-κB signals lead to the same physiologic responses. In this review, we will describe the roles of various NF-κB proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
259
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(266 citation statements)
references
References 103 publications
(118 reference statements)
7
259
0
Order By: Relevance
“…[35][36][37] Genetic mouse models revealed that NIK is required for the proper development and/or maintenance of secondary lymphoid organs, for osteoclastogenesis, for T-cell activation as well for B-cell survival. 35,38,39 In this paper, we highlight an unexpected role for NIK in TNFR1-induced cell death. We found that NIK diverges from the alternative NF-κB pathway to promote cell death.…”
mentioning
confidence: 91%
“…[35][36][37] Genetic mouse models revealed that NIK is required for the proper development and/or maintenance of secondary lymphoid organs, for osteoclastogenesis, for T-cell activation as well for B-cell survival. 35,38,39 In this paper, we highlight an unexpected role for NIK in TNFR1-induced cell death. We found that NIK diverges from the alternative NF-κB pathway to promote cell death.…”
mentioning
confidence: 91%
“…Osteoclasts, originate from hematopoietic progenitors, are essential for bone homeostasis, and play a vital role in both the development of osteoporosis and the metastasis of tumors to bone. The formation of osteoclasts involves several factors such as receptor activator of nuclear factor-kappaB (NF-kappaB) ligand (RANKL) and macrophage colony-stimulating factor (Novack, 2011). Many researchers have shown that RANKL is directly involved in the differentiation of macrophages into osteoclasts (Wang et al, 2003;Kukita and Kukita, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Receptor activator of nuclear factor kappa-B ligand was reported to be the unique osteoclastogenesis cytokine promoting osteoclast formation (17,18,43). It has been suggested that osteoclast functional activity rather than formation is increased in primary osteoporosis and that dexamethasone acts to increase osteoclast formation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using the following tools: Receptor activator of nuclear factor kappa-B ligand is a tumour necrosis factor (TNF) family member produced and secreted by osteoblasts, which, through binding to its receptor (RANK) on progenitor and mature osteoclasts, regulates osteoclastogenesis and activation of osteoclasts in normal and pathological states of bone remodelling (17,18). Osteoprotegerin is a "protector of the bone" TNF receptor family member produced by osteoblasts that binds to RANKL and thereby blocks the RANKL-RANK interaction, inhibiting differentiation and activation of the osteoclasts (19), as illustrated in Fig.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%